2011
DOI: 10.1136/hrt.2010.220467
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of exercise-induced pulmonary hypertension in subjects with preserved left ventricular ejection fraction: implication of an increase in left ventricular filling pressure during exercise

Abstract: Exercise-induced PH provides prognostic information in subjects with preserved LV ejection fraction. The excess risk of exercise-induced PH is restricted to subjects with an increase in estimated LV filling pressure during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 37 publications
5
42
1
Order By: Relevance
“…Indeed, in a well-selected population of 55 such patients without PH at rest with a BNP assay within normal range and in stable hemodynamic conditions, Borlaug et al 49 found that exercise testing induced a consensual PCWP and end-diastolic pressure elevation in ≈50% of subjects. Similar observations were reproduced by Maeder et al 50 Furthermore, Shim et al 51 found that patients with HFpEF who had exercise-induced PH in the presence of elevated E/e′ had a higher rate of hospitalization or mortality. Like PH at rest, exercise-induced PH is not specific to HFpEF.…”
Section: Guazzi Pulmonary Hypertension In Diastolic Heart Failure 373supporting
confidence: 72%
“…Indeed, in a well-selected population of 55 such patients without PH at rest with a BNP assay within normal range and in stable hemodynamic conditions, Borlaug et al 49 found that exercise testing induced a consensual PCWP and end-diastolic pressure elevation in ≈50% of subjects. Similar observations were reproduced by Maeder et al 50 Furthermore, Shim et al 51 found that patients with HFpEF who had exercise-induced PH in the presence of elevated E/e′ had a higher rate of hospitalization or mortality. Like PH at rest, exercise-induced PH is not specific to HFpEF.…”
Section: Guazzi Pulmonary Hypertension In Diastolic Heart Failure 373supporting
confidence: 72%
“…Thus, our results support the presence of a sub-clinical LV diastolic dysfunction [24]. The presence and prognostic value of sub-clinical diastolic dysfunction has already been demonstrated in various diseases [25,26].…”
Section: Mechanisms Of Eiph In Sscsupporting
confidence: 75%
“…Nonetheless, changes in E/e 0 from rest to exercise still remain the most frequent measurement obtained during exercise in the clinical work-up of HFpEF, and provide strong prognostic insights. 9,16 As reported in Table 1, 3,7-11 the results of studies overall confirm that exercise E/e 0 increases on average more in suspected or confirmed HFpEF than in controls.…”
supporting
confidence: 78%